미생물 첨가가 느타리 버섯 폐배지의 영양소 함량, 발효성상 및 미생물상에 미치는 영향 - 김동현; 제연주; 이혁준; 아만; 민찬식; 김삼철; D. H. Kim; Y. J. Jae; H. J. Lee; Sadar M. Amanullah; C. S. Min; S. C. Kim (농업생명과학연구, 2013)
본 연구는 미생물 첨가가 느타리버섯 폐배지의 영양소 함량, 발효특성 및 미생물상에 미치는 영향을 조사하기 위해 수행하였다. 시험은 느타리버섯 폐배지에 미생물 무첨가구(CON), 고초균 첨가구 (Bacillus subtilis 2⨯1010 cfu/g; BS), 유산균 첨가구(Lactobacillus plantarum 2⨯1010 cfu/g; LP) 및 혼합균 첨가구(Bacillus subtilis : Lactobacillus plantarum = 1:1; BL)로 4 시험구를 설정하고 6일간 발효시켰다. 발효 직후 0, 1, 2, 4 및 6일에 시료를 채취하여 분석에 이용하였다. 발효 6일후 조단백질과 조지방 함량은 BS구에서 가장 높았다(P<0.05). NDF 함량은 LP구와 BL구에서, ADF 함량은 미생물을 첨가한 모든 시험구에서 높은(P<0.05) 반면, in vitro 건물소화율은 CON구가 높았다 (P<0.05). Lactate와 propionate 함량은 CON구와 BS구가 타 시험구에 비해 높았다(P<0.05). 한편 발효 0일에 유산균 함량은 BS구와 LP구에서 높았으며(P<0.05), 발효 1일에 유산균 함량은 LP구에서, 고초균 함량은 BL구에서 각각 높았다(P<0.05). 발효 2일에 lactate와 propionate 함량은 LP구와 BL구에서 타 시험구에 비해 높았다(P<0.05). 이상에서와 같이 BS 첨가는 발효과정 중 유기산 생성량 개선에는 유리하나 건물소화율에는 부정적인 영향을 미칠 것으로 사료된다. This study was conducted to know the effects of micro-organism supplementation on fermentation characteristic nutrient content and microbial count of spent mushroom substrate. Treatments were untreated mushroom substrate (CON), mushroom substrate treated with Bacillus subtilis (2⨯1010cfu/g; BS), Lactobacillus plantarum (2⨯1010cfu/g; LP) and combo (Bacillus subtilis : Lactobacillus plantarum = 1:1; BL). Mushroom substrates were incubated for 6 days. Samples were obtained at 0, 1, 2, 4 and 6 days of incubation for analyses. After 6 days of incubation, BS had highest crude protein and ether extract, but decreased in vitro dry matter digestibility (IVDMD) (P<0.05). The IVDMD was higher in CON (P<0.05). Concentrations of lactate and propionate was higher (P<0.05) in LP and BL at the initial stage (2 days) of fermentation. However, these results were not persisted at the end. After 6 days, CON and BS have had the higher (P<0.05) concentration of these two acids. Overall, BS improve organic acids production, but could decrease IVDMD.